Some studies on the physical properties and degradability of tapioca and corn starch low density polyethylene blends / K.NgaJib ... [et al.] - NgaJib, K.; Said, C.M.S; Tahir, H.; Din, M.R.M (2004)
Starch based plastics materials have potential to be used in various applications to reduce the use of nonrenewable and nondegradable petroleum based materials. In the present study the compatibility of starch as fillers in low density polyethylene plastic films was evaluated for the purpose of producing degradable plastic films for environmental and agricultural uses. Two different types of starch were used in the study namely: tapioca- and com-starch. Blends and films at various starch proportions were produced using Twin Screw and Blow Film Extruder respectively. Products were tested for their structural and mechanical properties using DSC, TGA and Tensile Tester. The degradable properties were determined using two methods namely, water absorption test and soil burial test. DSC analysis showed no significant change in the Tm of the blends as compared to the virgin LDPE. Tensile strength decreases with increasing starch content. Water absorption was found to increase with increasing starch content. TGA analysis of LDPE/starch films shewed that degradation had occurred in all blends. At least three degradation mechanisms were identified in the blends through TGA analysis. These were assigned to the mass lost due to moisture vaporization, the degradation of tile starch and the degradation of the LDPE. Tensile properties and and the starch content decreases after soil burial suggesting that some degree of biodegradation occur.